Radiogenic heat production of Variscan granites from the Western Bohemian Massif, Germany - Scharfenberg,L.; Regelous,A.; De Wall,H. (Journal of Geosciences, 2019)
Much of the Mid-European basement has been consolidated during the Variscan Orogeny and includes large volumes of granitic intrusions. Gamma radiation spectroscopic measurements in three study areas along the western margin of the Bohemian Massif give a record of radiogenic element concentrations in the Variscan granites. Most intrusions of the Fichtelgebirge (except for the Tin Granite) and intrusive complexes in the Bavarian Forest show Th/U ratios exceeding unity, most likely related to abundance of monazite. In contrast, some of the Oberpfalz granites located near the Saxothuringian-Moldanubian boundary (Flossenbürg, Steinwald and Friedenfels types) are characterized by higher uranium concentrations and thus Th/U < 1. The low Th/U ratios here are in agreement with a possible U mobilisation along the Saxothuringian-Moldanubian contact zone observed in previous studies. Heat production rates of granites in the three study areas vary between 3.9 and 8.9 µW/m3, with a mean of 4.9 µW/m3. This classifies the intrusions as moderate- to high-heat-producing granites. Considering the huge volume of granitic bodies in the Variscan crust of the Bohemian Massif, the contribution of in situ radiogenic heat production had to have a major impact and should be considered in further thermal modeling.
Keywords: Variscan granites; gamma spectrometry; heat production; Uranium; Thorium; Bohemian Massif